Electric field control of deterministic current-induced magnetization switching in a hybrid ferromagnetic/ferroelectric structure - Cai, Kai-Ming; Yang, Mei-Yin; Ju, Hailang; Wang, Sumei; Ji, Yang; Li, Baohe; Edmonds, K.W.; Sheng, Yu; Zhang, Bao; Zhang, Nan; Liu, Shuai; Zheng, Hou-Zhi; et al. (Nature Publishing Group, 2017)
All-electrical and programmable manipulations of ferromagnetic bits are highly pursued for the aim of high integration and low energy consumption in modern information technology1, 2, 3. Methods based on the spin–orbit torque switching4, 5, 6 in heavy metal/ferromagnet structures have been proposed with magnetic field7, 8, 9, 10, 11, 12, 13, 14, 15, and are heading toward deterministic switching without external magnetic field16, 17. Here we demonstrate that an in-plane effective magnetic field can be induced by an electric field without breaking the symmetry of the structure of the thin film, and realize the deterministic magnetization switching in a hybrid ferromagnetic/ferroelectric structure with Pt/Co/Ni/Co/Pt layers on PMN-PT substrate. The effective magnetic field can be reversed by changing the direction of the applied electric field on the PMN-PT substrate, which fully replaces the controllability function of the external magnetic field. The electric field is found to generate an additional spin–orbit torque on the CoNiCo magnets, which is confirmed by macrospin calculations and micromagnetic simulations.